P1723CLINICAL AND LABORATORY CHARACTERISTICS OF RENAL TRANSPLANT PATIENTS WITH AA AMYLOIDOSIS IN A TERTIARY CENTER IN TURKEY. (6th June 2020) - Bilgic, Ece; Eren Sadioğlu, Rezzan; Eyüpoğlu, Şahin; Kocaay, Akın fırat; TUZUNER, ACAR; Şengül, Şule; Keven, Kenan
Abstract: Background and Aims: Despite improved therapeutic regimens, AA amyloidosis is still associated with higher risk of mortality after renal transplantation (RT). Moreover the clinical, laboratory characteristics and prognostic factors remain poorly understood. We aimed to identify predictive parameters of prognosis, investigate the etiology, clinical and laboratory features of renal transplant patients with biopsy proven AA amyloidosis. Method: We conducted a retrospective study using twenty-eight renal transplant patients with AA amyloidosis and twenty-eight renal transplant control patients without amyloidosis matched for age and time after transplantation that were regularly followed in University of Ankara School of Medicine Nephrology Department between October 2018-October 2019. Causes of AA amyloidosis, treatment (colchicine and/ or anti-interleukin (IL) 1 treatment) and number of Familial Mediterranean Fever (FMF) attacks in the last year in case of FMF, biochemical values such as mean CRP, hemoglobin, serum albumin, proteinuria, glomerular filtration rate (GFR), serum creatinine levels were compared between groups. Results: In amyloidosis and non-amyloiodosis group, the mean age was 44±13 and 44±12 years; 57% and 54% were males, mean time after transplantation was 95±64 and 93±12 month, respectively. FMF was found as the most common cause of AA amyloidosis (86%). All FMF patients received colchicine and eight (33%) FMF patients with AA amyloidosis with insufficient response to colchicine were treated with anti-IL-1 agents. The mean colchicine dose was 0, 92±0, 34 mg/day. The mean GFR were 63±24 ml/dk/1, 73 m 2 in amyloidosis and 71±19 ml/dk/1, 73 m 2 in non amyloidosis group, (p=0.195). The most important finding of present study was significantly higher CRP levels in patients with AA amyloidosis compared to non-amyloidosis group (15, 12±15, 16 mg/L vs 6, 59±8, 20 mg/L, p=0, 011, respectively). Conclusion: In this study, we found higher CRP levels in renal transplant patients with AA amyloidosis which indicates persistent ongoing chronic inflammation among these patients. Figure: Clinical and Laboratory Characteristics of Patient Groups